2021
DOI: 10.1017/s0266462321000106
|View full text |Cite
|
Sign up to set email alerts
|

Overview of information retrieval in a hospital-based health technology assessment center in a Swedish region

Abstract: Objectives This article aims to provide a brief review of information retrieval and hospital-based health technology assessment (HB-HTA) and describe library experiences and working methods at a regional HB-HTA center from the center's inception to the present day. Methods For this brief literature review, searches in PubMed and LISTA were conducted to identify studies reporting on HB-HTA and information retrieval. The description of the library's involvement in the HTA center and its wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Other experiences with HB-HTA, i.e., IMPlementation of A Quick hospital-based HTA (IMPAQHTA) in the Lombardy Region (Italy) in 2017, have shown that allowing for a rapid assessment and the provision of relevant information that hospital managers need for making investment decisions in health technologies are some of the key features of a wholesome and implementable HB-HTA framework [ 20 ]. Stadig et al (2021) also approached the issue of the availability of relevant information by describing the practices of data retrieval, underlining the involvement of librarians [ 21 ]. These elements were reflected in our research as benefits (sorting out and making sense of available data/information) and obstacles (insufficient time to conduct an HB-HTA assessment).…”
Section: Discussionmentioning
confidence: 99%
“…Other experiences with HB-HTA, i.e., IMPlementation of A Quick hospital-based HTA (IMPAQHTA) in the Lombardy Region (Italy) in 2017, have shown that allowing for a rapid assessment and the provision of relevant information that hospital managers need for making investment decisions in health technologies are some of the key features of a wholesome and implementable HB-HTA framework [ 20 ]. Stadig et al (2021) also approached the issue of the availability of relevant information by describing the practices of data retrieval, underlining the involvement of librarians [ 21 ]. These elements were reflected in our research as benefits (sorting out and making sense of available data/information) and obstacles (insufficient time to conduct an HB-HTA assessment).…”
Section: Discussionmentioning
confidence: 99%